2019
DOI: 10.3390/rs11010070
|View full text |Cite
|
Sign up to set email alerts
|

How Well Can IMERG Products Capture Typhoon Extreme Precipitation Events over Southern China?

Abstract: This study assesses the performance of the latest version 05B (V5B) Integrated Multi-Satellite Retrievals for Global Precipitation Measurement (GPM) (IMERG) Early and Final Runs over southern China during six extremely heavy precipitation events brought by six powerful typhoons from 2016 to 2017. Observations from a dense network composed of 2449 rain gauges are used as reference to quantify the performance in terms of spatiotemporal variability, probability distribution of precipitation rates, contingency sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…Of course, more researches are needed for knowing the application potentiality of GSMaP_Gauge_NRT. The performance of the IMERG near-real-time products have been investigated in capturing extreme precipitation events [64,65]. The results of these studies indicated that the IMERG has a promising potential for monitoring typhoon rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, more researches are needed for knowing the application potentiality of GSMaP_Gauge_NRT. The performance of the IMERG near-real-time products have been investigated in capturing extreme precipitation events [64,65]. The results of these studies indicated that the IMERG has a promising potential for monitoring typhoon rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al [8] assess the performance of the latest version V5B of IMERG Early and Final Runs over southern China during six extremely heavy precipitation events. Observations from a dense network composed of 2449 rain gauges are used as a reference to quantify the performance in terms of spatiotemporal variability, probability distribution of precipitation rates, contingency scores, and bias analysis.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…Just like weather radar QPE, satellite rainfall retrieval is also an indirect measurement of rainfall. Many previous works [12,30,31] stated that satellite data would underestimate the magnitude of high rainfall rates. Hong et al [32] stated that satellite performance degrades with the increase of rain rate but has higher relative bias in the light rain.…”
Section: Introductionmentioning
confidence: 99%